Liability of the insured for the damage caused by themselves - Ilkić Zoran (Zbornik Radova: Pravni Fakultet u Novom Sadu, 2012)
The complexity of the relationships regarding traffic accidents in the case of a collision of motor vehicles is that the persons responsible, and very often damaged, often claim compensation for damages from the other party. Drivers often appear to be responsible to third persons in traffic, but also to each other, which further complicates the procedure of allocation of liability and damages. The author analyzes the grounds on which to identify the person responsible for the damages which is suffered by other people in our law system. At the same time, it points out to the incompleteness of the legislation on common liability, as well as the inconsistency in applying the provisions of consent to the infliction of harm.